Cognitive linguistics - Croft, William; Cruse, D. Alan (Cambridge Cambridge University Press, 2004)
Cognitive Linguistics argues that language is governed by general cognitive principles, rather than by a special-purpose language module. This introductory textbook surveys the field of cognitive linguistics as a distinct area of study, presenting its theoretical foundations and the arguments supporting it. Clearly organised and accessibly written, it provides a useful introduction to the relationship between language and cognitive processing in the human brain. It covers the main topics likely to be encountered in a course or seminar, and provides a synthesis of study and research in this fast-growing field of linguistics. The authors begin by explaining the conceptual structures and cognitive processes governing linguistic representation and behaviour, and go on to explore cognitive approaches to lexical semantics, as well as syntactic representation and analysis, focusing on the closely related frameworks of cognitive grammar and construction grammar. This much-needed introduction will be welcomed by students in linguistics and cognitive science.
Keywords: Cognitive grammar